Exploring the association between dietary indices and metabolic dysfunction-associated steatotic liver disease: Mediation analysis and evidence from NHANES - Qiang Wang; Rude Chen; Shaohua Chen; Bowen Wei; Chunlan Liu; Zongxing Jiang (PLoS ONE, 2025)
Background The association between dietary indices and metabolic dysfunction-associated steatotic liver disease (MASLD) has shown inconsistent results in previous studies. Additionally, the potential mediating variables linking dietary quality to MASLD have not been adequately explored. Methods We analyzed data from 6,369 participants in the National Health and Nutrition Examination Survey (NHANES) 2007–2018. Three dietary indices—Healthy Eating Index (HEI), Energy-adjusted Dietary Inflammatory Index (EDII), and Composite Dietary Antioxidant Index (CDAI)—were evaluated for their associations with MASLD using logistic regression models adjusted for a comprehensive range of covariates. Mediation analysis was performed to evaluate the roles of potential mediators from four domains: insulin resistance (homeostatic model assessment of insulin resistance, HOMA-IR; metabolic score for insulin resistance, METS-IR), systemic inflammation (systemic inflammatory response index, SIRI; systemic immune-inflammation index, SII), obesity or visceral fat distribution (a body shape index, ABSI; body roundness index, BRI), and oxidative stress (Gamma-Glutamyltransferase, GGT; Bilirubin; Uric Acid). Results After adjusting for all covariates, only HEI showed a consistent inverse association with MASLD, while EDII and CDAI showed no significant associations. Mediation analysis identified METS-IR, HOMA-IR, BRI, and ABSI as significant mediators in the relationship between HEI and MASLD, with mediation proportion accounting for 47.16%, 48.84%, 52.69%, and 13.84%, respectively. Conclusion Higher HEI is associated with a reduced risk of MASLD. The findings suggest that insulin resistance and visceral fat distribution partially mediate the relationship between HEI and MASLD, providing insights into potential mechanisms linking diet and liver health.